2002
DOI: 10.1046/j.1532-5415.2002.50254.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of Benzodiazepines Associated with Incident Disability?

Abstract: OBJECTIVES-This study examined the association between benzodiazepine use and incident disability with an emphasis on elucidating whether the underlying health conditions that result in benzodiazepine use (confounding factors) or intrinsic adverse effects of benzodiazepine use were responsible for functional decline. DESIGN-Cohort study with follow-up of 4 to 5 years. SETTING-A health maintenance organization (HMO) in western Washington.PARTICIPANTS-Individuals aged 65 and older from a random sample of HMO enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
3
39
3
Order By: Relevance
“…In a cross-sectional analysis, Ried et al found that benzodiazepines dispensed during the last year were positively associated with a total score including both IADL and ADL limitations, 20 although they did not distinguish between short-and long-acting drugs. Gray et al found a significant multiple adjusted association of benzodiazepine use with physical functioning but not with ADL 18 ; in a second larger study, however, they found a significant association with mobility and ADL 19 -the risk for ADL limitations being greater for shortacting agents. In another longitudinal cohort, Boudreau et al did not find an association with mobility.…”
Section: Duration Of Action and Indicationmentioning
confidence: 91%
“…In a cross-sectional analysis, Ried et al found that benzodiazepines dispensed during the last year were positively associated with a total score including both IADL and ADL limitations, 20 although they did not distinguish between short-and long-acting drugs. Gray et al found a significant multiple adjusted association of benzodiazepine use with physical functioning but not with ADL 18 ; in a second larger study, however, they found a significant association with mobility and ADL 19 -the risk for ADL limitations being greater for shortacting agents. In another longitudinal cohort, Boudreau et al did not find an association with mobility.…”
Section: Duration Of Action and Indicationmentioning
confidence: 91%
“…This previously published method allows for standardized conversion of doses of different anticholinergic medications into a single exposure measure so that we are able to capture overall anticholinergic burden. 28,29 …”
Section: Methodsmentioning
confidence: 99%
“…The authors suggested that the preferential use of benzodiazepines with short elimination half life is unlikely to reduce fall risk among older people taking benzodiazepines [Landi et al 2005]. Besides an increased risk for falls, benzodiazepine exposure in community-dwelling older people has been associated with several negative health consequences, including depressed mood [Patten et al 1996], impaired cognition [Hanlon et al 1998] and loss of physical function [Gray et al 2002].…”
Section: Hypnosedatives and Benzodiazepinesmentioning
confidence: 99%